Utilization of Google Apps for Education (GAFE) as a Learning Medium for Early Childhood - Rahmi, Siti; Wahyuni, Erna (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Many children have not been able to develop and share the work obtained during learning activities. This is due to the lack of media utilized by teachers that can help students in developing the works made during learning. Therefore, teachers need to make an innovation in the provision and utilization of learning media that can help students in developing competencies and the work they achieve. the purpose of this study is to determine the utilization of Google Apps For Education (GAFE) as a learning media for early childhood. The method used by researchers in conducting this research is a quantitative method, which is done through distributing online questionnaires to correspondents involved in this study. The results of this study indicate that the utilization of Google Apps For Education can be utilized as a means of learning media that can assist students in learning. The conclusion of this research is that Google Apps For Education can be used as a learning media that can be utilized for early childhood.